The history of economic thought : a reader - Medema, Steven G.; Samuels, Warren J., 1933- (London ; New York : Routledge, 2003)
This collection of readings covers the major themes that have preoccupied economic thinkers throughout the ages, including price detaermination and underpinnings of the market system, monetary theory and policy, international trade and finance, income distribution, and the appropriate role for government within the economic system.
Includes bibliographical references and index.
osc 25/04/14
Loans
Keywords: Economics -- History